TNFα-induced macrophage chemokine secretion is more dependent on NF-κB expression than lipopolysaccharides-induced macrophage chemokine secretion - Ciesielski, C; Andreakos, E; Foxwell, B; Feldmann, M (2002)
The transcription factor NF-κB is a pivotal intracellular regulator of many inflammatory responses and it has been proposed that it represents a potential therapeutic target. As chemokines are important for the progress of an inflammatory response by the recruitment of immuno-competent cells, the role NF-κB plays in TNFα- or lipopolysaccharides (LPS)-induced chemokine secretion by human monocyte-derived macrophages was examined. Secretion of the CXC chemokines IL-8, GROα and ENA-78, induced by TNFα, was significantly suppressed by inhibiting NF-κB, using overexpression of IκBα. However, when induced by LPS the expression of these chemokines was unaffected. In contrast, expression of the CC chemokines MIP-1α, MCP-1 and RANTES induced by TNFα or LPS was significantly inhibited by the overexpression of IκBα. Therefore, there appear to be different mechanisms regulating CC and CXC chemokine secretion by macrophages, depending on the stimulus and that TNFα and LPS can use different signaling mechanisms in macrophages to regulate chemokine synthesis.